Heat Transfer Enhancement Using Hybrid Nanoparticles in Ethylene Glycol Through a Horizontal Heated Tube - Adnan Mohammed, Hussein; M. M., Noor; K., Kadirgama; D., Ramasamy; M. M., Rahman (Universiti Malaysia Pahang, 2017)
Heating hybrid nanofluids by the mixing of solid nanoparticles suspended in liquid represents a new class of heat transfer enhancement. To enhance heat transfer for many industrial applications, a computational fluid dynamics modelling simulation using the finite volume method and adopting the SIMPLE algorithm was performed. The mixture of aluminium nitride nanoparticles into ethylene glycol which acts as a base fluid is considered as a new concept of hybrid nanofluids that can increase heat transfer. The hybrid nanofluid was prepared experimentally with a volume fraction range of 1% to 4%. The size diameter of nanoparticles, heat flux around a horizontal straight tube, and Reynolds number is approximately 30 nm, 5000 w/m2 and 5,000 to 17,000, respectively. The computational method had been successfully validated using available experimental data reported in the literature. It was found that 1% to 3% Aluminum nitride hybrid nanofluids can significantly affect efficiency, while more than 3% volume fraction are insignificant as they obtain less than one efficiency. Results show that a combination of aluminium nitride nanoparticles with the EG base fluid tends to augment heat transfer performance significantly.